English only please? students' views of their self-confidence in spoken English in a Philippine state university - Briones, Max Samson; Villegas, Kemart; Maroto, Philip Andre; Lleve, Jay; Sevillano, Jenny Ann (Yayasan Mitra Persada Nusantara, 2023)
Speaking in front of a crowd necessitates a great deal of courage and confidence in order to adequately explain and communicate your message to the audience. According to Inayah and Lisdawati (2017), students who struggle to speak in front of a large group of people frequently lack self-confidence. In regards, the researchers utilized a qualitative research approach, specifically Interpretative Phenomenological Analysis, in conducting this study. The study seeks to determine how students perceive their confidence in spoken English, as well as the precise tactics they use for confidence reinforcement. A total of 22 second year English major students, using semi-structured interview, the current study investigates their perceptions and views about their self-confidence in terms of spoken English in a Philippine State University as well as what certain techniques and approaches do they employ for confidence reinforcement. The results showed that majority of them were viewing themselves as mediocre users of the said language and are still in the process of learning. They are still working with their fluency as well as expanding their vocabularies. The most dominant learning approach students employ is the traditional way which includes reading books, novels and other literary works. Future researchers may investigate the students' oral recitation approach preference and conventional learning mediums which were not included in the current study.